Inhibition of a Myotoxic Phospholipase A2 isolated from Crotalus durissus cumanensis by Pentacyclic Triterpenes - Laura Cardona-Alzate; Lina Maria Preciado-Rojo; Isabela Barahona-Sanchez; Vanesa Cardona-Cartagena; Jaime Andres Pereañez (Vitae)
BACKGROUND: Ophidian accidents have been recognized as public health events in Colombia since 2004 and have been systematically reported since 2007, constituting a significant public health problem. One of the components present in the venoms of Viperidae snakes is the phospholipase A2 (PLA2) enzyme, playing a fundamental role in snakebite poisoning and responsible for many of the local effects that are not neutralized by antivenoms, the only treatment approved for the management of these accidents. Traditional herbal treatments hold promise, with ethnopharmacological studies emphasizing compounds, particularly pentacyclic triterpenes, as potential inhibitors of PLA2. OBJECTIVE: To identify compounds with the potential to reduce or neutralize the local effects generated by PLA2, present in the venom of snakes of the Viperidae family, the major cause of ophidian accidents in Colombia. METHODS: Four triterpenic compounds (madecassic acid, ursolic acid, betulinic acid, and oleanolic acid) were evaluated to determine the inhibitory capacity on the enzymatic activity of myotoxic phospholipase A2, extracted from Crotalus durissus cumanensis venom and purified by RP-HPLC. To determine the inhibitory capacity of the compounds against the enzymatic activity of PLA2, the synthetic monodisperse substrate 4-nitro-3- (octanoloxy) benzoic acid was used. Molecular docking was also performed to identify by visual inspection the interactions between the compounds and the active site of the enzyme. RESULTS: The highest percentage of inhibition was presented by ursolic acid (47.01%). This is supported by the results of the molecular docking, where this compound was found to have interactions with Leu2, Phe24, Tyr52, and Lys69, amino acids involved in the catalytic activity of the enzyme. CONCLUSIONS: Ursolic acid was determined as the most promising compound among the four evaluated against the local effects generated by PLA2. Future studies may be performed to determine other potential benefits of these compounds versus other biological actions of the enzyme.